Examining the utility of lower dose radiotherapy for localised primary ocular adnexal MALT lymphoma. Issue 3 (6th March 2021) - Leeson, Sarah; Jayamohan, Jayasingham; Vu, Hanh; Sundaresan, Puma
Abstract: Introduction: Most primary ocular adnexal lymphomas are those involving mucosa‐associated lymphoid tissue (MALT). Radiotherapy (RT) dose regimens in the literature vary from the historically used high doses (up to 56 Gy) to lower dose RT. We aimed to examine our institution's experience with the use of orbital RT for treating early‐stage primary ocular adnexal MALT lymphoma (POAML). Methods: Patients treated for stage I or II POAML over a 12‐year period (July 2006 to June 2018) were identified through institutional databases. Data were retrospectively collated through review of patient records. Descriptive statistical methods were employed to analyse the data. Results: Eighteen patients (median age of 67; range 44‐87yrs) with localised POAML (3 cases of bilateral disease) were identified, resulting in a total of 21 evaluable orbits. Eight (44%) patients were female, and all were documented to be of good performance status (ECOG 0‐1). The median follow‐up was 34 months (range 8‐75 months). The commonest dose fractionation used was 20 Gy in 10 fractions ( n  = 13 orbits) and a 3D conformal or volumetric modulated arc therapy (VMAT) technique was used in the majority of cases. None of the patients experienced an in‐field recurrence. One patient had experienced a contralateral orbital recurrence two years post‐unilateral orbital RT for orbital MALT lymphoma. Three patients experienced distant relapse. Conclusion: The use of lower dose orbital RT such as 20 Gy in 10 fractions (or radio biologically equivalent) yields excellent local disease control in the management of ocular adnexal MALT lymphoma. The durability of the response appears to be favourable. Given the indolent nature of the disease and the low levels of toxicity associated with lower dose orbital RT, this regimen remains our favoured approach to the management of localised POAML. Abstract : We aimed to examine our institution's experience with the use of orbital RT for treating early‐stage primary ocular adnexal MALT lymphoma (POAML).The use of lower dose orbital RT such as 20 Gy in 10 fractions (or radio biologically equivalent) yields excellent local disease control in the management of ocular adnexal MALT lymphoma.